THE EFFECTS OF SOCIALIZATION, TAX COMPLIANCE, AND TAX COLLECTION ON LAND AND BUILDING TAX REVENUE (PBB-P2) IN THE REGIONAL TAX DIVISION I OF THE REGIONAL REVENUE AGENCY (BAPENDA) OF BATAM CITY - Prastika, Lilis Oktavia; Sabri, Sabri; Sumardin, Sumardin (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the influence of socialization, taxpayer compliance, and tax collection on Rural and Urban Land and Building Tax (PBB-P2) revenue in Regional Tax Sector I of the Regional Revenue Agency (Bapenda) of Batam City. The study used a descriptive, quantitative approach with a population of 323,830 PBB-P2 taxpayers and a sample of 100 respondents selected via simple random sampling. The instrument, in the form of a questionnaire, has been tested for validity and reliability, with all items demonstrating both. The results of the t-test show that socialization has a significant effect on PBB-P2 revenue (t count = 5.034; sig. = 0.000), taxpayer compliance has a considerable impact (t count = 8.191; sig. = 0.000), and tax collection also has a considerable effect (t count = 7.944; sig. = 0.000). Multiple linear regression analysis yields the equation Y = 5.163 + 0.090X₁ + 0.379X₂ + 0.981X₃, with a determination coefficient (R²) of 0.530, indicating that these three variables explain 53% of the variation in PBB-P2 revenue. The simultaneous F test shows a significant influence of the three independent variables on PBB-P2 revenue (F count = 98.537 > F table = 2.93; sig. = 0.000). This study emphasizes the importance of integrating socialization, compliance, and collection in increasing PBB-P2 revenue in Batam City.